Covid-19 and maxillo-facial fractures: A comprehensive retrospective cohort study on the analysis of costs in COVID-19 era - Yeğin, Mehmet Emre; Gur, Ersin; Tiftikcioğlu, Yiğit Özer; Songür Kodik, Meltem (Journal of Surgery and Medicine, 2022)
Background/Aim: Maxillofacial trauma management has also undergone a change starting from December 2019 due to the emergence of a new viral infection, later called COVID-19, and then a pandemic mandating new medical protocols. This retrospective cohort study aimed to explain the changes in medical costs and underlying causes of cases with maxillofacial bone fractures during the COVID-19 period, based on the lack of focus on cost analyses on this subject in previous studies. Methods: Patients who were operated on for maxillofacial trauma in our clinic before and during the COVID-19 outbreak were retrospectively analyzed in terms of sex, age, etiology, personal protective equipment (PPE) usage, treatment methods, and total costs. Statistical analyses were carried out for any significant changes. Results: A total of 78 patients of which 38 were operated on before whereas 40 were operated on during the COVID-19 outbreak, were included in this study. Accordingly, 24 patients of the pre-COVID-19 group and 37 patients of the post-COVID-19 group were admitted from Emergency Department (ED), which included all the first wave patients (n=21). In the pre-COVID-19 group, a total of 220 screws and 58 plates were used for 22 IRFs. The total LoH of the patients was 180 days. In the post-COVID-19 group, 274 screws and 70 plates were used for 24 IRFs. The total LoH of the patients was 185 days. A total of 156 PPE including N95 masks and extra operation shirts were used. The pre-COVID-19 group’s treatment costs were calculated as USD 320.3 per patient. Post-COVID-19 group’s treatment costs were calculated as USD 496.68 per patient. Conclusion: The statistical evaluations revealed that the COVID-19 pandemic resulted in differences due to the introduction of PCR tests applied for each patient and the PPE used for the precautions taken for the COVID-19 infections. On the other hand, there were no changes in the number of the use of plates, screws, and in the length of hospitalization. It can be argued that this outcome has led to no necessary changes in the treatment protocols in terms of costs.